Application of four-dimension criteria to assess rigour of qualitative research in emergency medicine - Forero, Roberto; Nahidi, Shizar; De Costa, Josephine; Mohsin, Mohammed; Fitzgerald, Gerry; Gibson, Nick; McCarthy, Sally; Aboagye-Sarfo, Patrick (BMC health services research, 2018)
Background The main objective of this methodological manuscript was to illustrate the role of using qualitative research in emergency settings. We outline rigorous criteria applied to a qualitative study assessing perceptions and experiences of staff working in Australian emergency departments. Methods We used an integrated mixed-methodology framework to identify different perspectives and experiences of emergency department staff during the implementation of a time target government policy. The qualitative study comprised interviews from 119 participants across 16 hospitals. The interviews were conducted in 2015–2016 and the data were managed using NVivo version 11. We conducted the analysis in three stages, namely: conceptual framework, comparison and contrast and hypothesis development. We concluded with the implementation of the four-dimension criteria (credibility, dependability, confirmability and transferability) to assess the robustness of the study, Results We adapted four-dimension criteria to assess the rigour of a large-scale qualitative research in the emergency department context. The criteria comprised strategies such as building the research team; preparing data collection guidelines; defining and obtaining adequate participation; reaching data saturation and ensuring high levels of consistency and inter-coder agreement. Conclusion Based on the findings, the proposed framework satisfied the four-dimension criteria and generated potential qualitative research applications to emergency medicine research. We have added a methodological contribution to the ongoing debate about rigour in qualitative research which we hope will guide future studies in this topic in emergency care research. It also provided recommendations for conducting future mixed-methods studies. Future papers on this series will use the results from qualitative data and the empirical findings from longitudinal data linkage to further identify factors associated with ED performance; they will be reported separately.